PENGARUH KONSENTRASI KITOSAN TERHADAP AKTIVITAS ANTIBAKTERI DENGAN METODE DIFUSI AGAR (SUMUR - Fibra Nurainy; Samsul Rizal; Yudiantoro Yudiantoro (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2008)
The aim of this work was to obtain the minimal concentration of chitosan which possess antibacterial characteristic. The concentrations of chitosan that used were 0%; 0,2%; 0,4%; 0,6%; and 0,8% (w/v), whereas bacteria cultures used to examine antibacterial activity of chitosan were Escherichia coli, Bacillus subtilis and Staphylococcus aureus. Well method (gel diffusion) was utilized to test the chitosan antibacterial activity. The result was analyzed using descriptive method and presented in the graphic form. The result showed the activity of chitosan restraint as antibacterial. The test of chitosan antibacterial activity utilizes gel diffusion (well) method. The data analyzed descriptively and presented in the graphic form. The result showed the activity of chitosan restraint as anti bacteria against Staphylococcus aureus, Bacillus subtilis or Escherichia coli with the highest restraint diameter was noticed at the addition of 0,2% chitosan, which were 20,27 mm/mg chitosan, 24,50 mm/mg chitosan and 31,53 mg chitosan, respectively. The lowest restraint diameter was found at the addition of 0,8% chitosan, which were 6,82 mm/mg chitosan, 12,14 mm/mg chitosan and 14,23 mm/mg chitosan, respectively. Keywords: Antibacterial activity, chitosan, gel diffusion method